Exploring environmental, economic and social aspects of rainwater harvesting systems: A review - de Sá Silva, Ana Carolina Rodrigues [UNESP]; Bimbato, Alex Mendonça [UNESP]; Balestieri, José Antônio Perrella [UNESP]; Vilanova, Mateus Ricardo Nogueira [UNESP] (Elsevier, 2022)
Rainwater harvesting systems (RWHS) can significantly contribute to the sustainability of cities and rural areas. In addition to their more obvious benefits (such as the ability to supply water in a decentralized manner, increasing local water security), several other benefits such as better stormwater management can be obtained through the use of these systems. This article summarizes the main benefits and barriers to the dissemination of RWHS, based on an extensive literature review. RWHS can reduce electricity use and greenhouse gas emissions when compared to public/centralized supply systems; however, the occurrence and magnitude of this reduction depend on the characteristics of both the public system and the RWHS, and should be analyzed locally. Stormwater runoff and associated problems can also be reduced by the used of RWHS, and the system tank/storage capacity is a key parameter to measure this benefit. Rainwater quality issues are influenced both by local characteristics and RWHS ones, including the roof type. Some of the main factors influencing the acceptance and dissemination of RWHS are economic (indicating the importance of financial incentives), lack of technical knowledge about the systems and a better perception of the real water availability in areas served by public water networks.
Keywords: Climate change; Sustainable cities; Urban water; Water supply; Water-energy nexus